Upaya Meningkatkan Hasil Belajar IPS Melalui Pembelajaran Berbasis Media Gambar - Legina Legina (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This research aims to improve IPS learning outcomes in cooperative materials through image-based media learning. Subjects in this study were the fourth grade students of SD Negeri 010099 Silau Maraja district Faithful Promise academic year 2016/2017. Result of learning process after research through picture as learning media at cycle I reach average value 70,7 with classical learning completeness reach 78%. Learning outcomes in cycle II reached an average value of 85.15 with the percentage of learning completeness classical reach 85%. It can be concluded that there is an increase of IPS learning outcomes in cooperative materials through media-based learning picture of fourth grade students of SD Negeri 010099 Silau Maraja district Faithful Promise academic year 2016/2017. Keywords: images, cooperatives Abstrak: Penelilitian ini bertujuan untuk meningkatkan hasil belajar IPS pada materi koperasi melalui pembelajaran berbasis media gambar. Subjek dalam penelitian ini adalah siswa kelas IV SD Negeri 010099 Silau Maraja kec. Setia Janji TP. 2016/2017. Hasil proses belajar setelah penelitian melalui gambar sebagai media pembelajaran pada siklus I mencapai nilai rata-rata 70,7 dengan ketuntasan belajar klasikal mencapai 78%. Hasil belajar pada siklus II mencapai nilai rata-rata 85,15 dengan persentase ketuntasan belajar klasikal mencapai 85%. Dapat disimpulkan terdapat peningkatan hasil belajar IPS pada materi koperasi melalui pembelajaran berbasis media gambar siswa kelas IV SD Negeri 010099 Silau Maraja kec. Setia Janji TP. 2016/2017. Kata kunci: gambar, koperasi